THE POTENCY OF BUNIDA F1 AND THEIR CROSSBREED (BUNIDA F2) AS SUPERIOR LOCAL CHICKEN - Rahmi, Annisa; Baharun, Abdullah; Adinda Putri, Tivanka (BRIN - Badan Riset dan Inovasi Nasional, 2024)
High market demands for animal protein have encouraged the optimization of local chicken genetic resources. This research aims to determine the potency of BUNIDA F1 chickens and their crossed-breed (BUNIDA F2). Five BUNIDA F1 hens at 12 months of age are inseminated with Bresse’s semen until they get 50 eggs. The eggs are incubated at 37-38°C and 60-70% humidity. The egg’s fertility and embryo devel-opment were observed on the 4th, 7th, and 18th days of incubation with the candling method. The parameters observed were egg weight, egg fertility, hatchability, and hatching weight. The results show BUNIDA F1 potencies are 54.12 ± 2.70 g egg weight, 82.59 ± 5.11% fertility rate, 71.14 ± 10.67% for hatchability, and hatching weight of BUNIDA F2 is 37.86 ± 1.97 g. It can be concluded that BUNIDA F1 and BUNIDA F2 have the potency to be developed into superior local chickens.